2021
DOI: 10.1038/s41596-021-00587-1
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical imaging and computational analysis of three-dimensional vascular network architecture in the entire postnatal and adult mouse brain

Abstract: This protocol uses vascular corrosion casting, hierarchical synchrotron radiation µCT imaging, and computational image analysis to assess the threedimensional vascular network architecture in the entire adult and postnatal mouse brain.TWEET New protocol for 3D hierarchical imaging (#µCT, #synchrotron) and computational analysis of the entire mouse brain vasculature @KrembilRI @ETH_en @UZH_en

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 174 publications
0
21
0
Order By: Relevance
“…3e,f ). Whereas sprouting angiogenesis and ETCs advance in a radial manner during embryonic development 88 , postnatally, ETCs spread in all directions of the various cortical layers, mostly emanating from the main vessel branches established during brain embryogenesis 3 , 153 , 154 (Fig. 3e,f ).…”
Section: Angiogenesis and Brain Developmentmentioning
confidence: 99%
“…3e,f ). Whereas sprouting angiogenesis and ETCs advance in a radial manner during embryonic development 88 , postnatally, ETCs spread in all directions of the various cortical layers, mostly emanating from the main vessel branches established during brain embryogenesis 3 , 153 , 154 (Fig. 3e,f ).…”
Section: Angiogenesis and Brain Developmentmentioning
confidence: 99%
“…3 b and c, generated from 10-day-old (P10) wild-type (WT) mice (Wälchli et al 2017 ). In their recent work, Wälchli et al ( 2021 ) showed that vascular density increases from postnatal to adult mouse brains (Wälchli et al 2021 ).
Fig.
…”
Section: Implantation Techniques Initial Trauma and Chronic Outcomementioning
confidence: 99%
“…Therefore, scanning an entire human organ (with a size of 5–30 cm in each dimension) at multiple resolutions can be executed without dissecting the sample or requiring to transport to different instrument locations or facilities 27 , 28 , 30 . HiP-CT features a customized flat-field correction, an attenuation scanning protocol, along with an efficient tomographic sampling and stitching pipeline to cover large, soft-tissue organs entirely, without staining 27 , 31 or clearing 10 . The integrated single-modality, multiscale imaging approach of HiP-CT 26 ensures a simplified image registration procedure thanks to the consistent tissue contrast across lengthscales.…”
Section: Background and Summarymentioning
confidence: 99%